Formulation and Characterization of Size Reduced Oral Extended Release Metformin Tablets - Prakash Tiwari, Om; Prakash B.N. Gupta, Surya; Upmanyu, Neeraj; Chikmath, Nagesh; Datta Murthy, V.S. (Asian Journal of Chemistry, 2010)
The present study describes the newer cost-effective formulation of metformin extended release tablets. Metformin is one of the widely used drugs for the management of type-II diabetes and is a large dose drug. The total average weight of the commercially available tablets was more than 750 mg. Size reduced oral extended release tablets were meant to increase patient compliance particularly for use in geriatrics. The aim of the present study is to formulate metformin extended release tablets of lower weight and size. Size reduced tablets of metformin extended release, were prepared by incorporating newer combination of pH dependent polymers like Keltone HVCR and EPO 100 in small quantities so as to reduce the size of the tablet and at the same time extending the drug release to the maximum duration of time. Dissolution profiles were studied using basket model according USP XXIV. Different medium of buffer pH 1.2, pH 4.5 and pH 6.8 phosphate buffer were used. The release was found to be following zero-order, first-order, Higuchi and peppa's model.